Knowledge and Practice of Injection Safety among Nurses Working in Tertiary Health Science Institute of Eastern Nepal - Rayamajhi, Sarobara; Thapa Pachya, Ambika (Journal of Karnali Academy of Health Sciences, 2023)
Background: Unsafe injections occur routinely in most developing world regions, implying a significant potential for the transmission of blood-borne pathogens. Unsafe injections account for a significant proportion of all new hepatitis B and C infections. This study explores the factors affecting knowledge and practices and to carry out observations in selected sample. Material and Methods: A descriptive cross-sectional study design was conducted among 143 nurses working at selected wards of BPKIHS using a self-administered questionnaire from nurses of the Medical, Surgical, Emergency, Orthopedic, ICU, SICU, Gynecology, Antenatal, and Postnatal wards. The nurses were selected using population-proportionate stratified random sampling. Observation of the 30 injection procedure was carried out. The data was analyzed using descriptive and inferential statistics. Results: The mean age of the respondents was 25.48±3.66 years. Poor knowledge was seen among 33.6%, and good knowledge was seen among 66.4% of the respondents. Similarly, good practice was observed among 11.2% and excellent practice was observed among 88.6% of the respondents. Significant association was found between knowledge and total work experience (p 0.023), vaccination against hepatitis B (p<0.001) Conclusion: The study concluded that one third of the nurses had good knowledge regarding injection safety. Majority of the nurses had excellent practice. The major lacking was seen related to the steps to be taken immediate after needle stick injury, practices of recapping the syringes and Hepatitis B vaccination coverage. Further participatory observation studies are required to explore factors related to the knowledge and practices of safe injection practices.